Declaring Tafseer for Humanity: Tafseer Methodology of Hassan Hanafi - Miftahuddin Miftahuddin (Millati: Journal of Islamic Studies and Humanities, 2020)
The purpose of this study is to construct the tafseer methodology of Hassan Hanafi in which he applies a new way of reading texts. The methodology used in this research is descriptive method using content analysis of literature. The main finding of this article is the existence of a new model of reading the text (Qur’an) offered by Hassan Hanafi in his Tafseer method. The uniqueness of the Tafseer methodology is the effort to incorporate social reality into the text. Departing from this reality, the text is "engineered" to overcome humanitarian problems. Thus the meaning of the text is directed to provide theological direction for efforts to solve human problems. In Hassan Hanafi's view, the text must be the theological foundation for humanitarian action. The essence of his specific view is that Tafseer does not pretend to seek universal meaning, but it looks for the temporal meaning that the Qur'an gives to certain generations by ignoring past and future interests. This kind of Tafseer always refers to the experience of Tafseer and its contemporary problems which put more emphasis on solving human social problems (al-manhaj al-tafsir al-ijtima'i) in the present context. The original aspect of this research is the reconstructing of Hassan Hanafi's thoughts in understanding the Qur'an progressively in opposition to the main mainstream Tafseer of the Qur'an in Muslim circles.